POLA KERUSAKAN PERMUKIMAN LERENG MERAPI PASCA ERUPSI MERAPI 5 NOPEMBER 2010 DI KECAMATAN CANGKRINGAN - , SYAFRUDIN, Prof. Ir. Sudaryono, M.Eng., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Merapi eruption on 5 November 2010 is one of the largest eruptions recorded in the history of Merapi. One of the affected areas is the sub-district of Cangkringan, Sleman regency. This research has some questions such as " as to whether the patterns of settlements damage after the eruption of Merapi, the settlements condition before and after the eruption, and the relationship between pattern of settlements damage to the pattern of eruption disaster". This study uses deductive-qualitative method. Deductive method is used as a foundation and guidance in the field, qualitative methods is used in the analysis and discussion. The pattern of damage after the eruption of Merapi settlements November 5, 2010 in sub-district of Cangkringan, tends to form basic cilcular and geometric linear. Basic circular patterns occurs uniformly on a radius of ± 8 km from the summit of Merapi, while the geometric linear patterns occurs in the flow of great rivers. The damage reaches ± 30% of all areas of Cangkringan. After the eruption, the sub-district of Cangkringan changed. At radius of ±8 km from the summit of Merapi, settlements were destroyed and gone. There were changes in land elevation due to lava piles in the Gendol River watershed, this is a secondary danger Merapi eruption, that is a cold lava flow during heavy rains. Meanwhile, the people who lost their homes at slopes of Merapi, remain stay in locations around the disaster, even a partial re-occupy their village.. The pattern of eruption disaster gives shape to pattern of damage to settlement on the slopes of Merapi. The pattern of eruption disaster is determined by the distribution pattern of hot clouds and lava. The distribution of these two volcanic marterial likely to lead to all directions at a radius of ± 8 km from the summit of Merapi, and slid away into the flow of rivers and valleys. In connection with this, and because the Merapi eruption occurred periodically, the flow of Gendol river needs to be re-formed to accelerate the formation of the natural river flow, this flow is necessary as the glide path of volcanic material so not spread to settlements. The area in a radius of ± 8 km from the summit of Merapi, the valleys which are facing directly to the top of Merapi, and the watershed of major rivers, not made as a permanent settlements by people of slopes Merapi.